Determinants Of E Wallet Loyalty In Indonesia: The Mediating Role Of Satisfaction - Mohammad Adrian; Mahrinasari MS; Dorothy RH Pandjaitan (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the determinants of e wallet loyalty in Indonesia by testing the effects of service quality, ease of use, usefulness, cost, and security, with user satisfaction as a mediating variable. A quantitative cross sectional survey was conducted using a five point Likert questionnaire distributed through Google Form to 300 active e wallet users in Indonesia from 18 February to 1 March 2026. The data were analyzed with SmartPLS 4 using the PLS SEM approach. The measurement model met the requirements of convergent validity, discriminant validity, and reliability. The structural model explained 79.6 percent of the variance in satisfaction and 78.6 percent of the variance in loyalty. The results show that service quality, ease of use, usefulness, cost, and security each have a positive and significant effect on satisfaction. Service quality, ease of use, cost, security, and satisfaction also have a positive and significant effect on loyalty, whereas usefulness does not directly affect loyalty. However, satisfaction significantly mediates all antecedent relationships with loyalty. Security is the strongest direct predictor of loyalty, while ease of use is the strongest predictor of satisfaction. The findings indicate that loyalty in e wallet services is shaped not only by functional performance but also by a secure and satisfying user experience.